Utilização de bens de capital em hospitais: uma abordagem a partir do Índice de Rendimento Operacional Global dos Equipamentos – IROG - Brand, Jose Paulinho (Universidade do Vale do Rio dos Sinos, 2014)
This work aims to contribute for the development and improvement of the management of hospital organizations. In this sense, the present work deals with the issue of improving the utilization of capital assets of hospitals, by adopting the concept of Index Global Operating Income ( IROG ). It also aims to propose a model of economic management to assess the efficiency of high-tech equipment in hospitals which enables the maximization of capacity utilization in order to increase the gain of the company, with the same fixed assets. Thus, the work was structured through a multiple case study, applied in the Moinhos de Vento Hospital. There were, therefore, the analysis and measurement of the IROG of two devices in order to verify the possibility of increasing the productivit, the ability to quickly meet demand and identify key stops and failures during examinations in two distinct areas of the hospital namely: Angiography and Image Diagnostic Units. The elements used for the method development were: a) consulting the theoretical framework on the topic; b ) definition and application of the method in two distinct areas of business; c ) contributions of managers and employees from areas; d) Contributions from the author of the work. The main results obtained by applying the method were : i ) obtaining the measurement and verification of low IROG index in two capital equipment;, ii ) greater clarity and insight of managers of areas in relation to efficiency of use of equipment; iii ) identification of the main reasons for equipment downtime; v) simulation scenarios for improving the efficiency of equipment and presentation of financial gains; vi ) introduction of measurement indicators IROG in respect of the hospital. Finally, the subject studied may evolve, especially in organizations focused on improving its operational processes and action plans to establish a systematic process for continuous improvement of their management.
Keywords: Lean in health; Waste; Restrictions; Index of global operating income; Competitive advantage; Efficiency ratio; Hospital management; Lean na saúde; Índice de rendimento operacional global; Vantagem competitiva; Gestão hospitalarÍndice de eficiência; Desperdícios; Restrições; ACCNPQ::Ciências Sociais Aplicadas::Administração